Hubungan nilai D-dimer terhadap mortalitas pada pasien COVID-19 derajat berat di RSUD Dr.pirngadi Medan tahun 2020-2021 - Fifi Nur Faltehal; Hapsah Hapsah (Pusat Riset dan Inovasi Nasional, 2023)
Coronavirus is an infectious human disease caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). D-dimer affects the mortality rate of COVID-19 patients due to an impaired immune system and an excessive inflammatory process that leads to tissue damage, leading to death conditions. The increase in COVID-19 severity correlates with an elevation in D-dimer levels. Elevated D-dimer levels have become an important marker in monitoring the condition of severe COVID-19 patients, as they are associated with worse outcomes and increased mortality in severe COVID-19 cases. To determine the relationship between D-dimer levels and mortality in severe COVID-19 patients.This research used a descriptive and analytical study with a cross-sectional design to determine the correlation between D-dimer levels and mortality in severe/critical COVID-19 patients. Data were obtained from secondary sources of medical records of confirmed severe/critical COVID-19 patients at Dr. Pirngadi Regional General Hospital. There is a correlation between D-Dimer levels and mortality in confirmed severe COVID-19 patients with moderate severity. A significant association exists between elevated D-Dimer levels and mortality in confirmed COVID-19 patients with moderate severity. This study also indicated that there are more male COVID-19 patients compared to females. Older individuals (elderly) in this study, aged over 45 years, are more likely to be infected with COVID-19 compared to those under 45 years of age.